Factors associated with metabolic syndrome and quality of life of adults in a northeast brazilian municipality - Santos, Isleide Santana Cardoso; Boery, Rita Narriman Silva de Oliveira; Fernandes , Josicélia Dumêt; Rosa, Randson Souza; Ribeiro, Ícaro José dos Santos; Souza, Andréa dos Santos (Revista Cuidarte, 2021)
Introduction: Metabolic Syndrome (MS) is currently considered a multi-factorial disease related to the asymptomatic, insidious, and deleterious inflammation that predisposes the individual to vulnerability by aggregating cardiovascular risk markers. Objective: to analyze the factors associated with Metabolic Syndrome and Quality of Life (QOL) in adult users of a health unit.  Material and Methods: a cross-sectional study carried out with 108 adult users. Data collection was performed using a sociodemographic, clinical, and metabolic structured questionnaire and The Medical Outcomes Study 36-item Short-Form Health Survey (SF-36) questionnaire. For the diagnosis of Metabolic Syndrome, the following criteria were used: increased abdominal circumference and arterial hypertension, diabetes, hypertriglyceridemia, and low HDL-cholesterol. Statistical analysis was performed using the Statistical Package for Social Sciences (SPSS) 21.0 software. Results: Metabolic Syndrome was identified in 88.0% of the adults. Of this total of users evaluated with the syndrome, 87.4% of the individuals were female; 71.7% had diabetes; 87.0% had arterial hypertension; sedentary lifestyle was identified in 53.7%. In the assessment of the BMI, overweight and obesity predominated in 68.4% and 24.9%, respectively. The domains with the lowest quality of life scores were General Health and Vitality. Conclusions: The study made it possible to identify the Metabolic Syndrome in most of the adults evaluated. There was a low perception of quality of life among adults in all domains, except for physical aspects and vitality. Thus, there is a need for surveillance and health education for the studied population and improvement of their quality of life.How to cite this article: Santos, Isleide Santana Cardoso; Boery, Rita Narriman Silva de Oliveira; Fernandes, Josicélia Dumêt; Rosa, Randson Souza; Ribeiro, Ícaro José dos Santos; Souza, Andréa dos Santos.  Factors associated with metabolic syndrome and quality of life of adults in a northeast brazilian municipality.   Revista Cuidarte. 2021;12(2):e.1678 http://dx.doi.org/10.15649/cuidarte1678
Keywords: Metabolic Syndrome; Quality of life; Diabetes; Hypertension; Obesity; Dyslipidemia